2022
DOI: 10.3390/vaccines10020159
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Coverage against Influenza and SARS-CoV-2 in Health Sciences Students during COVID-19 Pandemic in Spain

Abstract: Vaccination against influenza and SARS-CoV-2 is recommended in health sciences students to reduce the risk of acquiring these diseases and transmitting them to patients. The aim of the study was to evaluate how the pandemic influenced the modification of influenza vaccination coverage during the 2019/2020 and 2021/2022 campaigns and to analyze the vaccination coverage against SARS-CoV-2 in health sciences students. A cross-sectional study was conducted among students of the Faculty of Nursing, Physiotherapy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…It is a much better result than the results from a study conducted in Slovakia, where the coverage was 71.7% ( 18 ). A study of January 2022 in Spain got similar results, with 97.8% of students being vaccinated ( 19 ). They also found that the coverage against influenza was higher in students vaccinated against COVID-19 (35.5 vs. 14.3%).…”
Section: Discussionmentioning
confidence: 65%
“…It is a much better result than the results from a study conducted in Slovakia, where the coverage was 71.7% ( 18 ). A study of January 2022 in Spain got similar results, with 97.8% of students being vaccinated ( 19 ). They also found that the coverage against influenza was higher in students vaccinated against COVID-19 (35.5 vs. 14.3%).…”
Section: Discussionmentioning
confidence: 65%
“…In the United States [14], high scores on attitudes and knowledge were achieved by 74.3% of medical students, 62.7% of pharmacy students, 57.1% of doctoral nursing students, and 24.7% of undergraduate nursing students. The authors conclude that negative attitudes, lack of knowledge and general discomfort exist in all programs, but in relation to vaccination, they occur especially in nursing [14], as opposed to the results obtained in Portugal and Spain [11][12][13]. In this sense, it is important to highlight that some factors can interfere with the effectiveness of the health planning process, namely behavior.…”
Section: Discussionmentioning
confidence: 92%
“…All enrolled students, regardless of year, were invited to complete the Scale of "Attitudes and Behaviors in Relation to Vaccination among Students of Health Sciences" (ACVECS-according to its Spanish initials) [10]), previously translated by two translators, which resulted in an overlapping translation. The ACVECS scale, which aims to measure health students' attitudes and behaviors with regard to vaccination, is made up of 24 items, the first 15 of which measure the "attitudes" dimension and the last 9, "behaviors" [10][11][12][13]. These 24 items were answered on a five-point Likert-type scale, ranging from 0 = strongly disagree to 4 = strongly agree.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations